(untitled) (Transactions of the Association of European Schools of Planning, 2021)
This issue (5.1) of Transactions of AESOP brings together a selection of papers submitted to recent rounds of the Best AESOP Congress Paper Award and an invited paper by Tuna Taşan-Kok the Chair of the AESOP Congress Paper Award Committee. They provide original and insightful contributions addressing key themes in contemporary planning research and practice.